Impact of processing on surface structure of human cardiac valve allografts - Krs, Otakar; Slízová, Dása; Burkert, Jan; Spatenka, Jaroslav; Hottmar, Petr (Acta medica (Hradec Kralove), 2004)
Methods of processing and cryopreservation are believed to be the most important factors of long term clinical performance of biological heart valve prostheses. That is why we decided to cooperate in evaluating the impact of current AHV (allograft heartvalve) bank protocol on valve tissue morphology. AHV harvested from "heart-beating" cadaveric donors, considered as a fresh tissue, were compared with valve samples from non-heart beating donors, samples stored in saline, samples treated with antibiotic solution, and finally with cryopreserved valves, stored in liquid nitrogen for months. All samples were dissected, dried with hexamethyldisilazane (HMDS) method, gold-coated, studied and photographed in scanning electron microscope Tesla BS 301. Different superficial patterns were found on ventricular and vascular surfaces of "fresh" semilunar valves. We were able to detect early changes of endothelium after harvesting, denudation of endothelial covering during preservation with and without freezing. Our alternative method of drying samples by HMDS method proved to be suitable for thin membranes of human semilunar valves. Scanning electron microscopy seems to be helpful for morphological control of processing, cryopreservation and liquid nitrogen storage of AHV. We believe that further confrontation of morphological investigation with other methods helps us to develop more suitable protocol of handling AHV in heart valve banking.
Keywords: srdeční chlopně; kryoprezervace; chlorid sodný; Tissue Preservation; Sodium Chloride; uchovávání tkání; Humans; Cryopreservation; Anti-Bacterial Agents; Microscopy, Electron, Scanning; lidé; aortální chlopeň; antibakteriální látky; Heart Valves; Pulmonary Valve; mikroskopie elektronová rastrovací; Aortic Valve; plicní chlopeň